ESTILOS DE CRIANZA E INTELIGENCIA EMOCIONAL EN LOS NIÑOS DE LA ESCUELA LEÓN DE FEBRES CORDERO DE LA PARROQUIA SAN JUAN - ALVARIO FRANCO FABIANA MAKERLY (2024)
The objective of this curricular integration work is to determine the influence of different parenting styles on the development of emotional intelligence in children from the León de Febres Cordero school in the San Juan parish. In this way, to carry out the research, in the first instance, the scientific contributions of different authors who talk about the two variables to be investigated were investigated, to later implement the use of the psychology interview and the application of psychological tests prevalence questionnaire in styles. parenting and emotional intelligence test for children up to twelve years of age. In addition, a non-experimental descriptive methodology was incorporated since the degree of relationship between both variables will be described, which will not be manipulable, thus achieving the initially stated objective. In the same way, the process for obtaining information is based on respect for the rights of the participants, risks were minimized and timely psychological care was provided so that the children did not present both psychological and physical problems during the duration of the research. Finally, the findings of the research were communicated. impartially and without bias, ensuring the integrity of the data and citing all sources appropriately. The results were shared with the educational community in a responsible manner and with due respect.